2022
DOI: 10.3390/rs14132964
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and Attribution of Earlier Start of the Growing Season over the Northern Hemisphere from 2001–2018

Abstract: The start of the growing season (SOS) is a vital ecological indicator for climate change and the terrestrial ecosystem. Previous studies have reported that the SOS over the Northern Hemisphere (NH) has experienced remarkable changes in the past few decades. However, because of the different spatial and temporal coverages of existing SOS studies, a coherent and robust account for SOS changes in the NH has been lacking. Using satellite-retrieved vegetation-phenology datasets, ground observations, and several aux… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 60 publications
2
1
0
Order By: Relevance
“…However, it is noteworthy that, at a regional level, a distinct trend of a delayed SOS has been evident across the majority of the regions in northeastern North America in recent decades. This observation aligns with previous research findings, indicating a gradual weakening of the carbon sink capacity in these regions [25].…”
Section: Temporal and Spatial Trends In Vegetation Photosynthetic Phe...supporting
confidence: 93%
See 2 more Smart Citations
“…However, it is noteworthy that, at a regional level, a distinct trend of a delayed SOS has been evident across the majority of the regions in northeastern North America in recent decades. This observation aligns with previous research findings, indicating a gradual weakening of the carbon sink capacity in these regions [25].…”
Section: Temporal and Spatial Trends In Vegetation Photosynthetic Phe...supporting
confidence: 93%
“…Utilizing long-term photosynthetic phenology data, we have identified a significant advancement in the SOS within northern terrestrial ecosystems. This observation is based on a comprehensive analysis of photosynthetic phenology, aligning with prior studies that employed greenness indicators to investigate a similar trend [25,26]. In particular, Chen et al ( 2022) found a slightly different magnitude, noting a 2.08-day average advancement in the SOS over the NH during 2001-2018.…”
Section: Temporal and Spatial Trends In Vegetation Photosynthetic Phe...supporting
confidence: 72%
See 1 more Smart Citation